A cross - layer design for video transmission with TFRC in MANETS - Christos Bouras; Vaggelis Kapoulas; Apostolos Gkamas; G Kioumourtzis; George Adam (International Conference on Data Communication Networking - DCNET 2012, Rome, Italy, 2012)
Mobile Ad hoc NETworks (MANETs) are becoming more essential to wireless communications due to growing popularity of mobile devices. However, MANETs do not seem to effectively support multimedia applications and especially video transmission. In this work, we propose a cross-layer design that aims to improve the performance of video transmission using TCP Friendly Rate Control (TFRC). Our design provides priority to video packets and exploits information from the MAC layer in order to improve TFRC?s performance. The proposed cross-layer mechanism utilizes Signal to Noise Ratio (SNR) measurements along the routing path, in order to make the route reconstruction procedure more efficient. Simulation results show that both the use of traffic categorization and the SNR utilization lead to important improvements of video transmission over the mobile Ad hoc network. More specifically, simulations indicate increased average Peak Signal to Noise Ratio (PSNR) for the received video, increased throughput and packet delivery ration, as well as reduced average end-to-end delay.